The Effect of Pyeloplasty on Renal Cortical Thickness in the Pediatric Population with Ureteropelvic Junction Obstruction - Asif Khan; Muhammad Rashid Ullah; Nizamuddin; Syed Mumtaz Ali; Fazli Elahi (Gandhara University, 2023)
OBJECTIVES To determine the effect of pyeloplasty on renal cortical thickness in the pediatric population with ureteropelvic junction obstruction (UPJO).  METHODOLOGY This retrospective study examined the renal cortical thickness in 100 pediatric patients diagnosed with ureteropelvic junction obstruction (UPJO). The study employed a non-probability consecutive sampling technique to select participants. Inclusion criteria encompassed children below five years of age, of both genders, with Pakistani nationality, and availability of both pre-and post-operative ultrasound data. Cases presenting with ureterovesical junction obstruction or vesicoureteral reflux were excluded from the analysis. Data collection involved gathering information on age, gender, and cortical thickness, with renal cortical thickness assessed through ultrasonography. A paired t-test was employed to compare the renal cortical thickness between the preoperative assessment and the 3-month follow-up. RESULTS The females were 40(40%) and males were 60(60%).  The mean age was 33.51±22.91months.  The mean cortical thickness before pyeloplasty was 5.23±0.93mm and 8.25 ± 2.34mm after pyeloplasty. The renal cortical thickness in both genders significantly increased to 3mm (p<0.001). The cortical thickness before pyeloplasty was 5.23±0.93mm, and after was 8.25±2.34mm.  CONCLUSION Renal cortical thickness can be improved after pyeloplasty in patients with ureteropelvic junction obstruction.